Computational quest, synthesis and anticancer profiling of 3-methyl quinoxaline-2-one-based active hits against the tyrosine kinase - Priyadarsini Raj; Abiseik Samuel; Anitha Kothandapani (SpringerOpen, 2024)
Abstract Background Cancer is the predominant cause of mortality and a remarkable obstacle to elevating life anticipation in every nation on globe. Hepatocellular carcinoma (HCC), a hyper-vascular tumour, develops and progresses due to angiogenesis, a key feature of malignancy. HCC exhibits high neoangiogenic activity because of the need to generate new blood vessels for tumour growth. Methods The present work includes the construction of virtual library of ligands, virtual screening using the Dockthor-VS server, ADMET study using the SwissADME and Osiris property explorer. All the synthesized compounds were characterized by UV, IR, NMR and mass spectroscopic techniques. MTT assay was done to find the IC50 of the synthesized compounds against HepG2 cell line. The more active compound found is subjected to the molecular dynamics simulation study. Results The ligands exhibited good docking scores, ADMET profile compared to the reference drugs. The target compounds were obtained with the satisfactory yields of 66-82%. The best activity against the HepG2 cancer cell line is observed with the compound SA-4 with IUPAC name (2-(3-methyl-2-oxoquinoxalin-1(2H)-yl)-N-(5-(3-nitrophenyl)-5H-thiazolo[4,3-b] [1,3,4] thiadiazol-2-yl) acetamide). The experimental results obtained show correlation with the in silico results. MD simulation of the compound SA-4 indicates the moderate stability of the protein-ligand complex in real time environment. Conclusion The results obtained suggest that the compound SA-4 has the potential to be a promising anticancer agent effective against the VEGFR-2 and FGFR-4. Graphical abstract